1999
DOI: 10.1034/j.1399-3003.1999.14c12.x
|View full text |Cite
|
Sign up to set email alerts
|

Airway epithelium expresses interleukin-18

Abstract: Interleukin(IL)-18 is an interferon (IFN)-c-inducing cytokine suggested to be important in regulating inflammatory responses. This study investigated the pulmonary expression of IL-18 under conditions characterized by T-helper (Th)1 (lipopolysaccharide (LPS) treatment/sarcoidosis) and Th2 (ovalbumin (OVA) challenge/asthma) cytokine production.In situ hybridization and immunocytochemistry were used to determine the number of cells expressing IL-18, IFN-c, IL-5 and major basic protein (MBP) within lung tissue fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
80
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 30 publications
6
80
1
1
Order By: Relevance
“…IL-18 mRNA and IL-18 protein, mainly consisting of pro-IL-18, were found to be constitutively expressed within the lung. This is in agreement with earlier studies, which showed that IL-18 mRNA is expressed in lungs and other organs of normal mice (21,28,(32)(33)(34). Alveolar macrophages, the resident phagocytes within the airways, are likely important producers of IL-18 within the lung, because IL-18 is known to be mainly produced by activated macrophages (19).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…IL-18 mRNA and IL-18 protein, mainly consisting of pro-IL-18, were found to be constitutively expressed within the lung. This is in agreement with earlier studies, which showed that IL-18 mRNA is expressed in lungs and other organs of normal mice (21,28,(32)(33)(34). Alveolar macrophages, the resident phagocytes within the airways, are likely important producers of IL-18 within the lung, because IL-18 is known to be mainly produced by activated macrophages (19).…”
Section: Discussionsupporting
confidence: 81%
“…Alveolar macrophages, the resident phagocytes within the airways, are likely important producers of IL-18 within the lung, because IL-18 is known to be mainly produced by activated macrophages (19). Cameron et al (32) reported that the majority of IL-18 mRNA within lung tissue of mice was localized to airway epithelium cells, although inflammatory cells, mostly lymphocytes, within the airway wall and parenchyma also expressed IL-18 mRNA. In addition, IL-18 mRNA expression was also found in granulocytes present in the lungs of LPS-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…We could not exactly verify that macrophages produce IL-12 in the serial sections of the frozen lungs because of weak IL-12 staining, but the distribution of IL-12 staining and macrophages closely overlapped beneath the bronchiolar smooth muscle coat suggesting that macrophages activated by influenza virus antigens produced mainly IL-12. While IL-18, TNF-α, and IFN-α, -β are produced not only by macrophages but also by non-immune cells such as epithelial cells, IL-12 is mainly produced by macrophages, monocytes, and dendric cells (D'Andrea et al, 1992;Cameron et al, 1999;Locksley et al, 2001;Pirhonen et al, 2001;Kashiwamura et al, 2002;Pirhonen et al, 2002;. Thus, the macrophage may be a key immune cell to induce early defense-immunity against influenza infection and IL-12 is dominantly produced in macrophages activated by influenza virus antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated enhanced expression of IL-12 (20 -22) and IL-12R (23,24) in sarcoid lungs. IL-18 expression was reported to be increased in the airway epithelial cells of sarcoid cases (25). However, the cooperative roles of IL-12 and IL-18 in sarcoidosis have not been fully resolved in Th1 response.…”
mentioning
confidence: 99%